NUMERICAL STUDY OF THE POSSIBILITY OF USING ADHESIVE JOINTS FOR INDIRECT MEASUREMENTS FOR STRESS DISTRIBUTION - Kisała, Piotr; Wiśniewski, Paweł (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The article covers the subject of examining adhesive joints usage in indirect stress distribution measurements, taking into account contemporary methods of stress distribution measurements, including testing with fiber optic stress sensors. Numerical methods, in particular the finite element method, were used to calculate the stress distribution. The research carried out is described taking into account the following order – firstly, preliminary assumptions regarding sample models and simulation parameters were presented, then the course of the simulation was described, and finally, an analysis of the obtained results was carried out. A control simulation was carried out on a base-glue-fiber sample, which, due to difficulties in assessing the stress characteristics, was retaken in order to calculate the strain convertible to stress. The final results, together with the coefficients defining the measure of compatibility of the characteristics, are presented in the form of graphs and a table.